A novel solar energy-based hydrogen generator integrated with battery storage - Gursoy, Mehmet; Dincer, Ibrahim (PERGAMON-ELSEVIER SCIENCE LTD, 2025)
Renewable energy generation enhances environmental carbon reduction, limits global warming, and addresses rising energy demand. This study is designed to meet the community's energy needs by producing electricity and hydrogen through the utilization of solar photovoltaic (PV) systems, energy storage, a unique hydrogen generator, and an on-site utility facility. The energy demand is balanced by a novel mathematical model, resulting in improved power output for the system. System Advisor Model (SAM) is employed for the development and testing of models. The effect of solar radiation on hydrogen production rates exhibits a linear trend, varying from 48.5 g/s in the absence of solar radiation to 48.501 g/s at a standard intensity of 1000 W/m2, underscoring the significance of solar intensity. The system achieves a hydrogen production rate of 153.95 tons per year and produces approximately 143,963 GWh of electricity annually, demonstrating its high-performance potential and significant energy output capacity. The energy and exergy efficiencies of the overall system were determined to be 30 % and 34.6 %, respectively.
Keywords: Battery; Efficiency; Energy; Exergy; Hydrogen generator; Storage; Solar energy; PV; SYSTEMS; OPTIMIZATION; DESIGN; Thermodynamics; Energy & Fuels